Growth of Black Orchids (Coelogyne Pandurata Lindl) with Additional Ecoenzyme Liquid Organic Fertilizer and Biostimulant of Cengkodok Leaf Extract - Zulfa Zakiah; Masnur Turnip (Jurnal Biologi Tropis, 2023)
Acclimatization of black orchid plantlets (Coleogyne pandurata Lindl.) with cengkodok leaf extract biostimulant treatment has been successfully carried out, but still have slow growth. To support growth and development at the enlargement stage, cultivated orchids need to be given eco enzyme liquid organic fertilizer (LOF) derived from various sources of organic matter. Provision of ecoenzyme LOF combined with biostimulant 20 mg/l of Cengkodok leaf extract to increase the efficiency of nutrient absorption. The aim of the research was to find the best type and concentration of LOF for the growth of black orchids at the enlargement stage. The study used a Complete Randomized Design (CRD) with two treatment factors namely type of LOF (ecoenzyme (ee) LOF from vegetable and fruit waste, ee LOF from pineapple peel waste, and "NASA" LOF) and . the POC concentration (0; 0.5; 1.0; and 1.5 ml/l). The results showed that the single treatment of ee LOF significantly effected the number of leaves and the number of black orchid tillers, while the single treatment of ee LOF concentration had an effect on the parameters of height, number of leaves, number of tillers and leaf area of black orchid. The parameter of chlorophyll content had no signifcant effect by the type and concentration of LOF. The largest leaf area was shown in the addition of ee LOF from vegetable and fruit waste at a concentration of 1 ml/l which was 11.88 cm2.